2010
DOI: 10.1002/uog.7509
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the prenatal diagnosis of congenital diarrhea

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Fetal bowel loop dilatation is an uncommon finding that has been related to several conditions and is generally divided into obstructive and nonobstructive types . In most cases, prenatal bowel dilatation usually suggests an obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fetal bowel loop dilatation is an uncommon finding that has been related to several conditions and is generally divided into obstructive and nonobstructive types . In most cases, prenatal bowel dilatation usually suggests an obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Nonobstructive bowel dilatation is a rare entity and may be the result of intrauterine fetal compromise, congenital chloride diarrhea, Hirschsprung disease, congenital pseudoobstruction, and microvillous inclusion disease. Prenatal diagnosis is difficult and may consist of diffuse dilated bowel loops, polyhydramnios, and echogenic bowel . Microvillous inclusion disease is a fatal congenital disorder of the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, meconium within the bowel is hyperintense on T1-weighted images. With CCD, hyperintensity within the bowel is absent due to watery diarrhea [14]. In this case, we carried out MRI with 1.5T system MAGNETOM Symphony (Siemens Healthcare, Germany) as an adjunct to ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…With CCD, the Cl level in amniotic fluid rises, but this does not provide a definitive diagnosis [13]. In recent years, Colombani et al reported that MRI in addition to ultrasound findings helped to diagnose the condition [14]. …”
Section: Introductionmentioning
confidence: 99%